Composite Ni/NiO-Cr(2)O(3) Catalyst for Alkaline Hydrogen Evolution Reaction - Bates, Michael K. (J Phys Chem C Nanomater Interfaces, 2015)
We report a Ni–Cr/C electrocatalyst with unprecedented mass-activity for the hydrogen evolution reaction (HER) in alkaline electrolyte. The HER kinetics of numerous binary and ternary Ni-alloys and composite Ni/metal-oxide/C samples were evaluated in aqueous 0.1 M KOH electrolyte. The highest HER mass-activity was observed for Ni–Cr materials which exhibit metallic Ni as well as NiO(x) and Cr(2)O(3) phases as determined by X-ray diffraction (XRD) and X-ray absorption spectroscopy (XAS) analysis. The onset of the HER is significantly improved compared to numerous binary and ternary Ni-alloys, including Ni–Mo materials. It is likely that at adjacent Ni/NiO(x) sites, the oxide acts as a sink for OH(ads), while the metallic Ni acts as a sink for the H(ads) intermediate of the HER, thus minimizing the high activation energy of hydrogen evolution via water reduction. This is confirmed by in situ XAS studies that show that the synergistic HER enhancement is due to NiO(x) content and that the Cr(2)O(3) appears to stabilize the composite NiO(x) component under HER conditions (where NiO(x) would typically be reduced to metallic Ni(0)). Furthermore, in contrast to Pt, the Ni(O(x))/Cr(2)O(3) catalyst appears resistant to poisoning by the anion exchange ionomer (AEI), a serious consideration when applied to an anionic polymer electrolyte interface. Furthermore, we report a detailed model of the double layer interface which helps explain the observed ensemble effect in the presence of AEI. [Image: see text]